A rigorous analytical solution of interfacial stresses and overall stiffness of beam structures bonded with partially covered plates. (1st February 2020) - Long, Hao; Wei, Yueguang; Liang, Lihong
Highlights: l A rigorous analytical solution of interfacial stresses and overall stiffness of plated beams are obtained. l Influences of the plate and interface properties are systematically studied. l Limitation of the widely adopted assumption of the same curvature of host beam and plate is clarified. l Critical values of the plate and interface parameters indicating overall stiffness saturation are proposed. Abstract: Beam structures with partially covered plates have been widely used in macro members and micro devices, such as concrete beams with fiber-reinforced plastic (FRP) plates, aircraft structures with FRP patches and smart beams with actuators/sensors. Based on the two-parameter elastic foundation model and the classical Euler–Bernoulli beam model, a rigorous analytical solution of interfacial stresses and overall stiffness of plated beams is obtained, and influences of the interface and plate properties are presented. The limitation of the assumption of the same curvature of host beam and plate, which was widely adopted in previous studies, has been clarified. And the present solution is applicable to a wider range of interface and plate properties, especially for large values of plate thickness, plate modulus and interfacial stiffness, as well as small values of plate length. The saturation phenomenon of overall stiffness is observed in some cases, and critical values of the interface and plate parameters corresponding to the saturation limit of overall stiffness can be referred for design. The results can provide guidance for the optimal design of widely-used plated beams to prevent premature interfacial debonding and acquire better overall performance, such as higher stiffness with FRP plates or shape control with actuators, by manipulating the interface and plate properties. Graphical abstract: Image, graphical abstract